Hydrogeological features of a massif to be used as a nuclear repository - Wetten, Cristian; Grassi, José Ivan (Comisión Nacional de Energía Atómica; Argentina, 1987)
Fil: Wetten, Cristian. Universidad Nacional de San Juan. Instituto de Investigaciones Mineras; Argentina